1996
DOI: 10.1038/bjc.1996.630
|View full text |Cite
|
Sign up to set email alerts
|

Expression of oncoproteins and the amount of eosinophilic and lymphocytic infiltrates can be used as prognostic factors in gastric cancer

Abstract: Summary Preoperative staging of gastric cancer is difficult. Several molecular markers associated with initiation and progression of cancer seem promising for obtaining preoperative prognostic information. To investigate whether these markers are indicative especially for the presence of lymph node metastases in patients with gastric cancer, we have examined primary tumour specimens from 105 patients with primary adenocarcinoma of the stomach entered in a surgical trial. In this trial, lymph node status was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
24
3
2

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 18 publications
7
24
3
2
Order By: Relevance
“…In this study, the human surface antigen EpCAM was found to be such a target, being predominantly expressed on ( pre )malignant lesions of the stomach and esophagus and allowing specific gene transfer to gastric and esophageal cancer cells in vitro. In agreement with the study of Songun et al, 26 we observed no significant association between EpCAM expression and clinicopathological features of the tumors. Most likely, this is due to the high prevalence of high EpCAM expression in the gastric adenocarcinomas.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the human surface antigen EpCAM was found to be such a target, being predominantly expressed on ( pre )malignant lesions of the stomach and esophagus and allowing specific gene transfer to gastric and esophageal cancer cells in vitro. In agreement with the study of Songun et al, 26 we observed no significant association between EpCAM expression and clinicopathological features of the tumors. Most likely, this is due to the high prevalence of high EpCAM expression in the gastric adenocarcinomas.…”
Section: Discussionsupporting
confidence: 93%
“…In gastric epithelium the expression of Ep-CAM is low, and its increase is associated with very early stages of development of intestinal metaplasia (unpublished data). However, Ep-CAM loss associated with poor prognosis, as demonstrated in our earlier (Songun et al, 1996) and the present study, differs from previous observations of increased Ep-CAM expression associated with poor prognosis in breast cancer (Mirecka et al, 1995). Although not very strong, Ep-CAM mediated adhesions were able to suppress the scattering of cells embedded into matrigel (Litvinov, 1995).…”
Section: Discussioncontrasting
confidence: 56%
“…In the present study based on the MRC trial, as well as those described by Yu et al (1995) and Songun et al (1996), eosinophil infiltration has been graded into three groups: none or few, moderate or scanty, marked or numerous. Only Iwasaki et al (1986) described a more objective index: none, 5100 cells, 4100 cells.…”
Section: Clinicalmentioning
confidence: 84%
“…The improved prognosis associated with the presence of marked tumour-associated tissue eosinophilia (TATE) in two cancers at either end of the gut is interesting and merits further investigation even if this is only found in a small percentage (8% in the present study) of these gastrointestinal cancers. Abnormal recruitment of tissue eosinophils is encountered in a variety of medical conditions including specific malignancies e.g., Hodgkin's disease certain types of leukaemia (Ogata et al, 1998) and some solid tumours (Pretlow et al, 1983;Iwasaki et al, 1986;Bethwaite et al, 1993;Caruso et al, 1993;Yu et al, 1995;Leighton et al, 1996;Songun et al, 1996;Ono et al, 1997;Geisinger et al, 1998;Tajima et al, 1998;Hong et al, 1999;Nielsen et al, 1999;Moezzi et al, 2000). TATE may simply be a surrogate marker of a distinctive cytokine response to an infiltrative tumour.…”
Section: Clinicalmentioning
confidence: 99%
See 1 more Smart Citation